Managerial Risk-Taking Behavior: A Too-Big-To-Fail Story - Zardkoohi, Asghar (Journal of business ethics, 2018)
We examine the implications of the US government’s too-big-to-fail (TBTF) policy as it has been applied to banks. Using alternative measures of risk, we compare the risk-taking behavior of 11 TBTF banks, identified by the Comptroller of the Currency in 1984, to a number of non-TBTF banks. We provide both theory and new empirical evidence to support our argument that the TBTF policy leads management to significantly increase risk-taking, with no corresponding increase in performance. While prior studies have considered the effects of the TBTF policy on limited, but risk-related aspects of bank behavior, such as the cost of funds, our study provides direct evidence about the risk-taking behavior associated with the TBTF policy. Our study has important implications for the current political debate regarding the too-big-to-fail policy.